Calificación de operación y desempeño de la Balanza analítica Ohaus PA214 de un laboratorio nacional - Jara Rojas, Katherine Beatriz (2018)
The objective of this paper was to describe the operation and performance of the Ohaus Analytical Balance PA214, for which the descriptive, observational and experimental methodology was used. The work was divided into two stages, the first stage corresponds to the operation qualification, where the checkpoint parameters of the controls were evaluated, in the same way the operational tests were carried out among them: the repeatability, the eccentricity and the weighing. The second stage consists of the Performance Qualification, this describes the necessary procedure to demonstrate that the system works uniformly, under normal conditions, and allows the reproducibility of truthful results in time, in this test a weight control of two products was carried out Pharmacists from a national laboratory. Satisfactory results were obtained, determining that the team is qualified to perform the weighing work during the manufacturing process of the medicines. It is concluded that the operation and performance rating developed for the Ohaus Analytical Balance PA214 are in accordance with the established acceptance criteria